Superfoods: the power of nature on your plate - Palmeri, Rosa (Millenium - Journal of Education, Technologies, and Health, 2025)
The term 'superfood' is frequently used in scientific literature to describe foods that are both visually appealing and rich in energy (Jagdale et al., 2021). The UN's 2030 Agenda for Sustainable Development highlights the importance of utilizing regional crops as a key strategy to improve nutrition and sustainability, particularly in malnourished regions. In recent years, superfoods—also referred to as functional foods—have gained increasing attention (Gupta & Mishra, 2020). These are traditional foods rich in essential nutrients such as proteins, fiber, and vitamins, or bioactive compounds that offer notable health benefits and may help reduce the risk of chronic diseases (Daugherty, 2011; Tacer-Caba, 2019). According to data collected in August 2018, a search for the term "superfoods" yielded 191 results, including research articles, book chapters, and review papers. In comparison, the term "superfruits" produced 85 results in the ScienceDirect database (Gupta & Mishra, 2020). However, for the period between 2019 and 2025, the number of results has significantly increased to 1,163. Similarly, the term "functional foods" yielded 210,226 results in the Wiley database and 382,852 results in ScienceDirect for the period 1998–2017. More recent data from 2019 to 2025 indicate a further rise, with 460,415 results recorded in ScienceDirect. These findings suggest a notable divergence in the scholarly adoption and conceptual framing of the term "superfood" compared to "functional food" (Gupta & Mishra, 2020).